The Silk Road Journey in the Marketplace as the Modern Time Pilgrimage - Karki, Dhruba (Literary Studies, 2016)
The Silk Road journey embodies an individual's revelation, a universal process of transformation of consciousness. At times, people set for pilgrimages to holy sites; other times, they go on trekking through hills and mountains. Pilgrimages to sacred sites have been replaced by people's journey to discotheques, fashion centers and shopping malls in the marketplace in today’s corporate world. What binds them together is the transformation of consciousness along the journey from the terrestrial to the celestial sphere. Specific human, including pilgrimage and business trip become popular when people, ranging from children to adult across cultures make them significant parts of their lives. Sound and images of disco, jazz, hip-hop, and pop-rock have entered the streets and hotels in cities, from Lhasa to London, Shanghai to San Francisco, Karachi to Kathmandu, and Tokyo to New York. In today’s world of saturated media presence, images and icons of heroes and legends, motivated by commercial and popular appeal, are circulated with a greater speed, becoming simultaneously a shared mythic currency and continuity, the modern world embodiment of silk road business, and thus, crossing the East-West divide.